Causes of The Failure of The Reciprocating Bilge Pump in Supporting The Bilge Transfer Process on Mv. Amanah Halmahera Amc - Yunez Husen , Akbar; Zakiah, Diah; Nurdin, M.; Sibarani, Maurirz (Greenation International Journal of Engineering Science, 2023)
The reciprocating bilge pump is an important auxiliary device in the bilge system in the engine room which functions to pump bilge from the bilge tank or engine room gutter to the OWS (Oily Water Seperator) and forward it to the ship's overboard. Reciprocating bilge pump is a type of reciprocating pump (piston pump) which is widely used for pumping viscous liquids or water mixed with oil. This pump generally consists of a pump housing or pump cylinder in which there is a plunger or piston which works by moving from TMB (Bottom Dead Point) to TMA (Top Dead Point) to suck liquid into and push it back out of the cylinder. This study aims to find out the causes of the problems and the efforts that can be made on the reciprocating bilge pump so that it can restore the performance of the reciprocating bilge pump. The research method that the authors used in compiling this research is a qualitative descriptive research. While data analysis is to identify the data set that has been obtained, so that the data can be analyzed and the purpose is analyzed in order to get a clearer picture in the preparation of this research both from the problems and the final results. It is hoped that this research research can produce ideas, solutions and appropriate problem solving, both in observing and handling the problems raised in this research. Based on research on the reciprocating bilge pump at MV. Amanah Halmahera AMC this pump is not working. This is caused by the release of the piston head from the piston rod so that there is no pressure on the pump and the check valve does not work properly so that it is difficult for the fluid to be sucked into the pump chamber. To prevent this problem, it can be done by reinstalling the check valve and cleaning the check valve.